1978
DOI: 10.1128/iai.19.2.575-582.1978
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and toxicity of a ribosomal vaccine, acetone-killed cells, lipopolysaccharide, and a live cell vaccine prepared from Salmonella typhhimurium

Abstract: The protective and toxic properties of a ribosomal vaccine prepared from Salnonella typhimurium W118-2 were systematically compared with those of an acetone-killed whole cell vaccine, purified lipopolysaccharide, and living cells in CD-1 mice. Tests of graded immunizing doses of each vaccine against several challenge doses of live strain W118-2 showed that, although the protection given by ribosomes approached the levels of protection conferred by living organisms, acetone-killed cells administered in appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…These observations raised the possibility that the early appearing 3///~ T cells during infection with facultative intracellular microorganisms may serve as a first defense against microbial pathogens. Salmonella sp are also facultative intracellular pathogens, and cellular immunity is regarded as one of the most important defense mechanisms, although humoral immunity is also involved in the protection against Salmonella sp (44)(45)(46). Our data presented here indicate that the 3//8 T calls appear in the peritoneal cavity and liver at an early stage after intraperitoneal infection with an avirulent strain of S. choleraesuis.…”
Section: Discussionmentioning
confidence: 59%
“…These observations raised the possibility that the early appearing 3///~ T cells during infection with facultative intracellular microorganisms may serve as a first defense against microbial pathogens. Salmonella sp are also facultative intracellular pathogens, and cellular immunity is regarded as one of the most important defense mechanisms, although humoral immunity is also involved in the protection against Salmonella sp (44)(45)(46). Our data presented here indicate that the 3//8 T calls appear in the peritoneal cavity and liver at an early stage after intraperitoneal infection with an avirulent strain of S. choleraesuis.…”
Section: Discussionmentioning
confidence: 59%
“…However, the role of antibodies during different stages of infection, and particularly in protection, is still incompletely understood, despite the large number of results published on this matter [2]. Vaccination of resistant mice with either attenuated or killed Salmonellae induced protection against secondary infection with an otherwise lethal dose of virulent bacteria and this protection could be passively transferred to naive mice with serum [79][80][81]. In susceptible mice, however, the situation is different.…”
Section: B Cells and Antibodies In Immunity Against S Typhimuriummentioning
confidence: 99%
“…Many investigators indicated that the efficacy of salmonella ribosomal vaccines varies with mouse strains [2], and that contaminating lipopolysaccharide (LPS) exerted the major effect [3,4]. In addition, salmonella ribosomal vaccines can induce mouse protection comparable to that induced by immunization with 230 a sublethal dose of viable virulent S. typhimurium [5,6] or with viable cells of attenuated strains [7].…”
Section: Introductionmentioning
confidence: 99%